TINDAK PIDANA PEMBUNUHAN DALAM HUKUM PIDANA ISLAM DAN HUKUM PIDANA POSITIF - Hifni, Mohammad; Hibar, Ujang; Agustiawan, M. Nassir (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2023)
Islamic law is not prescribed for games and jokes. It is in accordance with the rules of the Shari'ah which fundamentally teach that the world is a place of testing and not eternal, while the Hereafter is a place of vengeance and eternal. Shari'ah also teaches that man is held accountable for his charity in the world and will be avenged in the Hereafter. The one who does good, the good will come back to him. If he does bad deeds, the ugliness will also come back to him. Therefore, punishment in the world will not remove punishment in the hereafter, unless he repents to God. The scholars of fiqh fatten down there are several punishments imposed on the perpetrators of this crime, namely: The original punishment, namely the law of qisas. This law is based on Allah's provisions in the Qur'an Surat Al Baqarah (2): 187) and (Q.S Al Maidah (5): 45) Substitute Punishment. According to fiqh scholars, if the punishment of qisas falls, for example forgiven or because there is peace, then there are two other substitute punishments, namely diyat borne by the murderer himself and the punishment of ta'zir. According to Imam al-Tahbrani, it is narrated from Amr bin Hazm Al-Anshari that the Prophet (peace be upon him) said: "The revenge of a deliberate murderer is qisas." If the heir forgives the murderer, the murderer is obliged to pay the diyat mughalazhah (big diyat) taken from the murderer's property. Supplementary Laws. In addition to the above punishments, in intentional murder there are other punishments, namely hindered inheritance rights, and hindered from obtaining a will from the victim. While in the positive criminal law the criminal sanction of murder in the Criminal Code there are several articles including the following: Article 338 reads: Whoever intentionally deprives another person of his life shall be punished with murder with a maximum imprisonment of fifteen years. Article 339 reads: Murder that is followed, accompanied, or preceded by a criminal act, committed with the intention of preparing or facilitating its execution, or to release oneself or other participants from the crime in the event of being caught, or to ensure the possession of goods obtained unlawfully, shall be punished with imprisonment for life or for a specified time, not more than twenty years. Article 340 reads: Whoever intentionally and premeditatedly deprives another of his life shall be punished with murder with premeditation, with the penalty of death or imprisonment for life or for a specified period of not more than twenty years